Effects of genetic drift and selection at larval stage resulting from hatchery practices in the Pacific oyster (Crassostrea gigas) - Taris, Nicolas; Sauvage, Christopher; Ernande, Bruno; Batista, Frederico; Boudry, Pierre (International Association for Genetics in Aquaculture (IAGA), 2006)
Hatchery techniques are now well handled in an increasing number of aquaculture species. However, unintentional effects of domestication often remain poorly documented. In this context, we studied how current hatchery practices may genetically influence larval traits for which significant genetic variation had previously been reported in the Pacific oyster. Two main factors were studied: culling (i.e. discarding the smallest larvae) and rearing temperature (26°C versus 20°C). In parallel, we estimated genetic diversity of broodstock populations sampled in French hatcheries. Finally, we compared larval development and settlement success in the progeny of one of these hatchery broodstock, which had been selected for seven generations, with those of wild oysters. Our results show that culling has a significant genetic influence, mainly through its effects on timing of settlement. Temperature also exerts a genetic effect as heritability estimates for larval growth are higher at 26°C than at 20°C. High temperature coupled with culling is therefore likely to increase response to selection for fast growing larvae. This hypothesis is supported by the comparison of larval development in progenies from hatchery versus wild broodstocks. Significant relatedness between hatchery parental oysters led us to propose that inbreeding depression affected part of this progeny. This fits with the high genetic load reported in the species. However, the remaining larvae exhibited faster growth and better settlement success than the wild ones. Effect of genetic drift and selection at larval stage resulting from hatchery practices will be discussed in the light of our results.